Research in Role of Creative Accounting Practices to Reduce Financial Risks in Jordanian Commercial Companies (Global Journal of Management and Business Research, 2022)
This research aimed to identify the role of creative accounting practices in reducing financial risks in Jordanian Commercial companies from credit and market risks and operating risks. to achieve the objectives of the study, a questionnaire was distributed to the study community consisting of accountants, financial schools, risk management directors, and managers of the accounting department in Jordanian industrial companies in various governorates of the Kingdom by way of a simple random sample of (300) individuals from 30 Commercial companies, and we chose a simple random sample. Of them (100) individuals, after the distribution of the questionnaire, (72) questionnaires were retrieved, and (72%) of the questionnaires retrieved the study relied on (One T-Test) to test the study hypotheses and achieve its goals. The study concluded a set of results, the most important of which is the presence of a statistically significant role for creative accounting practices to reduce financial risks in Jordanian Commercial companies related to credit risks, market risks, and operational risks. Among the most prominent recommendations of this study is the necessity of conducting more studies on the relationship between creative accounting methods and practices and risk reduction.